OFFSPRING AFFECTED ANGIE’S EXISTENCE IN MARRIAGE - Wahyuningtias, Diny (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2019)
This research used a novel titled "The Things We Do for Love" by Kristin Hannah. This research discussed the affected of offspring on women existence in a marriage that are reflected by the main character, Angie, in the novel. This research was conducted to know how offspring affects Angie's existence in her marriage. This novel tells the story of a man and a woman named Angie and Conlan, the main character in the novel. Their marriage ended in divorce because as a woman, Angie cannot give the child to her husband. The problem came to Angie when she knew she could not keep her pregnancy a few times, because she had a weak womb which makes Angie loses her existence as a woman, wife and mother. This research method used descriptive method. Where, the data presented related to the topic, and then explain it in detail. Data collected were analyzed using the ideas of Simone de Beauvoir (1949) in his book that addresses the issue Woman Existence and Julie Mitchell (2008) on Woman Revolution.